Vibration Analysis and Development of a Submersible Ultrasonic Transducer for an Application in the Inhibitory Activity of Pathogenic Bacteria - Kamonwan Srathonghuam; Benjamaporn Wonganu; Wutthikrai Busayaporn; Jatuporn Thongsri (My University, 2021)
Development of a new generation of a submersible ultrasonic transducer (SUT) using vibrational analysis aimed for higher efficiency and inhibitory activity of pathogenic bacteria has been presented. The SUT with a dual-stepped shape of front mass and PZT8 transducer working at 50W, 110V, 50 kHz has been examined by the plate counting method. It was found that the SUT could inhibit pathogenic bacteria, e.g., Escherichia coli, Salmonella typhi, Staphylococcus epidermidis, and Staphylococcus aureus. For the vibrational analysis, the results were derived from structural and acoustic simulations using harmonic response analysis (HRA) in ANSYS software. In the structural simulation, the results showed a natural frequency and total deformations both inside and outside of the original SUT corresponding to the results measured by a laser doppler vibrometer. The acoustic simulation, set up as an actual operation at different depths from the water surface, has been applied. The HRA revealed various distributions of acoustic pressure. For further distances away from the SUT, the acoustic pressure decreased. When the SUT has been submerged deeper into the media, the acoustic pressure becomes larger at positions close to the bottom of the tank. This discovery is consistent with power concentration measurement. For the development of the SUT, this research proposed other 5 models as the candidate to be investigated. The results from the acoustic simulation confirmed that the different shapes of the front mass provided different acoustic pressure distributions. The wider head of the front mass in the modified dual-stepped shape generated the highest acoustic pressure and was fully distributed through an all-over cleaning tank. Therefore, this proposed model is suitable for industrial commercialization and possesses the inhibitory activity of pathogenic bacteria.
Keywords: Pathogenic bacteria; Harmonic; Microbial Inactivation Methods